Pengaruh Interferensi Bahasa terhadap Cara Berbicara Bahasa Inggris Mahasiswa - Nirwana Darwis; Hasriati Nur (Institut Agama Islam Negeri (IAIN) Bone, 2021)
The purpose of this study was to find out what factors influence students' language interference in speaking English. This research used descriptive qualitative research. This research applied purposive sampling in selecting the samples. The participants of this research consisted of 43 students. The data were collected by using speaking tests, observations and interview questionnaires. The results of the student speaking test showed that there were some intonations that students used in speaking English did not match the intonation used by native speakers. The researchers also found that there were some words pronounced by students did not match the emphasis of the words. Based on the results of the second interview, the researchers concluded that there are three basic factors that influence students' language interference when speaking in English, namely the environment, geographical location, and culture. Keywords: language interference; English; speaking